Perilaku Tanah Lempung Yang Distabilisasi Dengan Abu Sekam Padi Dan Kapur - Adnan Ruziq Ihsan; Soewignjo Agus Nugroho; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
A Soil is usually as a base of both building construction and road construction, it becomes a problem if the soil has an inapproriate properties. Materials such as cement, lime, and rice husk ash can be used as stabilization materials to increase soil strength. This study examines the behavior of high plastically stabilized clay with cement, lime, and rice husk ash. The increases of soil performance is seen by CBR test, UCS test, and swelling potential measurements. CBR and UCS test were carried out with 4 conditions; 28 days ripening, 28 days ripening and 4 days immersion, tested directly, and 4 days immersion. The examination of swelling potential was supported by dial on soaked CBR and consolidometer. Soil samples from each varied mixture were loaded with various loads. The results showed that the CBR value and UCS value increase with the duration of ripening and decrease with the length of immersion. Then the CBR and UCS values increase with the addition of lime percentage in the mixture. The highest CBR and UCS values occurs in cement soil 90% + lime 10% with CBR values of 164.34% and UCS values of 1402.97 kPa in conditions for 28 days without immersion. The lowest CBR and UCS values occurs in cement soil 90% + rusk husk ash 10% with a value of 1.68% for CBR and 11.21 kPa for UCS values with conditions soaked for 4 days without immersion. The maximum expansion rate of each sample was reached at pressure of 3 kPa. Keywords: CBR, UCS, Lime, Rice Husk Ash, Cement, Clay, Stabilization